2016
DOI: 10.1155/2016/7803846
|View full text |Cite
|
Sign up to set email alerts
|

Medical Application of Spirulina platensis Derived C‐Phycocyanin

Abstract: Along with the development of marine biological pharmaceutical research, high-effective and low-toxic drugs and functional foods isolated from marine organisms have become a new field of pharmacy and bromatology. The pharmacological actions, such as anti-inflammation, antioxidation, antitumor, immunological enhancement, and hepatorenal protection of C-phycocyanin (C-PC) from Spirulina platensis, have been reported, and C-PC has important value of development and utilization either as drug or as functional food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 101 publications
(98 reference statements)
1
128
0
6
Order By: Relevance
“…Antioxidant capacity and phenolic content of fermented A. platensis F&M-C256 biomass Arthrospira has in vitro and in vivo antioxidant, radical scavenging and anti-inflammatory activities, principally due to the presence of phycocyanin and polyphenols (Bhat and Madyastha 2000;Abd El-Baki et al 2009;Liu et al 2016).…”
Section: In Vitro Digestibility Of Fermented a Platensis Fandm-c256 Bimentioning
confidence: 99%
“…Antioxidant capacity and phenolic content of fermented A. platensis F&M-C256 biomass Arthrospira has in vitro and in vivo antioxidant, radical scavenging and anti-inflammatory activities, principally due to the presence of phycocyanin and polyphenols (Bhat and Madyastha 2000;Abd El-Baki et al 2009;Liu et al 2016).…”
Section: In Vitro Digestibility Of Fermented a Platensis Fandm-c256 Bimentioning
confidence: 99%
“…Phycocyanin content of blue-green algae can be used as a functional food (Prasanna, Sood, Suresh, Nayak, & Kaushik, 2007; Abd El Baky, El Baroty, & Ibrahem, 2015;Liu, Huang, Zhang, Cai, & Cai, 2016). Spirulina platensis has been used as a dietary supplement in animals (Vonshak & Tomaselli, 2002).…”
Section: Iron)mentioning
confidence: 99%
“…Zeinab et al (2015) reported that administration of S. platensis on Nile Tilapia feed increases hemoglobin compared to control; suplementasi 10% S. platensis increase hematocrit value (Ibrahem et al, 2013). Spirulina platensis contains phycocyanin, detection routine examination revealed that the blood parameters of red blood cells, platelets and white blood cells in the normal range for animals treated phycocyanin (Liu et al, 2016). Research Moreira, Behling, Rodrigues, Costa and Souza-Soares (2013), in which malnourished rats supplemented with S. platensis LEB-18 for 30 days to get that increased hematological.…”
Section: Hematological Gurami Feed With Experimental Dietsmentioning
confidence: 99%
“…Certain algae, including A platensis , also contain other potentially active substances that belong to a family of phycobilins (in particular phycocyanobilin), which are linear tetrapyrrolic compounds related to human bile pigments, known to have strong antioxidant as well as antiproliferative properties . Phycocyanobilin linked to a specific protein moiety forms a molecule called C‐phycocyanin exerting potent biological effects, including anticancer activities . However, molecular mechanisms accounting for these antiproliferative effects are largely unknown.…”
Section: Introductionmentioning
confidence: 99%